Analisis Implementasi Pendidikan Multikultural Berbasis Agama Islam di MIN 01 Cilacap Sebagai Upaya Untuk Mengatasi Bullying - Awalia Putri Sofiya; Fatikhatul Khoiri; Nurul Mubin (DAS Institute, 2024)
This study aims to analyze the implementation of Islam-based multicultural education at MIN 01 Cilacap and its impact on students' social attitudes, particularly regarding tolerance and bullying prevention. Multicultural education is implemented indirectly through teaching and learning activities emphasizing mutual respect and care among students. Although some teachers do not explicitly understand the term multicultural, they have applied those values in their teaching practices. Research results show that this approach is effective in raising students' awareness of the importance of respecting differences and preventing bullying behavior. Multicultural values based on Islamic teachings, such as compassion, tolerance, and brotherhood, have been successfully implemented as the foundation of students' behavior in their daily lives. This shows that multicultural education can play an important role in shaping an inclusive and harmonious learning environment. Keywords: multicultural education, MIN 01 Cilacap, Islamic values, tolerance, respect, bullying, social attitudes